ANALISIS STRUKTURALISME GENETIK DALAM NOVEL MIDAH SIMANIS BERGIGI EMAS KARYA PRAMOEDYA ANANTA TOER - Nani Anggraini (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2019)
This study discusses how the world view according to the author in Pramoedya Ananta Toer's novel Midah Simanis Bergigi Emas based on genetic structuralism which covers the world view and collective subject and the surrounding environment and how the author views Pramoedya Ananta Toer's Midah Simanis Bergigi Emas novel based on reality history linked to the literary work. The method used in this research is descriptive analytical method. The analysis technique performed is dialectical technique, namely, prioritizing coherent meaning. Dialectic techniques develop two kinds of concepts, namely "whole-part" and "understanding -explanation". Sources of data in this study used primary data sources in the form of a novel entitled Midah Simanis Bergigi Emas by Pramoedya Ananta Toer. the creation of the Midah Simanis Bergigi Emas novel was lifted from a social problem that affected it. Genetic elements of the work of Sasta are worldview, author's relationship with historical reality, author's biography, application of novel genetic structuralism. The world view on genetic structuralism in the Midah Simanis Bergigi Emas novel is lifted from a social problem that influences its views on God, the world, and humans. The world view that triggers the subject to identify world views is considered as one of the characteristics of the success of a literary work in genetic structuralism.